Pengembangan Potensi Desa Wisata Teluk Mata Ikan Dalam Rangka Peningkatan Wisatawan Sebagai Pariwisata Keberlanjutan - Sihombing, Dame Afrina; Efendri, Abel Fadigra; Besar Hariyanto, Oda Ignatius (LPPM Universitas Internasional Batam, 2024)
Villages, as the lowest unit of government, play a crucial role in the national economy. Most of Indonesia's population lives in villages, so a strong foundation for economic growth should be built from the village level to achieve self-reliance and economic improvement of the community. Teluk Mata Ikan Tourism Village, located in Nongsa, Batam, is an attractive destination for tourists looking for an experience of nature and local culture. Teluk Mata Ikan Village offers the charm of stunning natural beauty and underwater life rich in marine life diversity. The village is surrounded by a stretch of clear blue sea, soft white sand and green tropical vegetation.